Cambios en los indices biológicos de la tararira, Hoplias malabaricus (Bloch, 1794) en un ciclo anual en la laguna Yalca, provincia de Buenos Aires, Argentina - Balboni, Leandro (2009)
The tararira is a top predator of paramount importance in Pampean lakes. The goal of this study is to assess the change of different biological indices of this species in Yalca Lake on a yearly basis. Also we attempt to determine the relationship between within indices variations and with water temperature (WT) and light hours (LH). Monthly captures were performed during 2006/2007 estimating the relative condition factor (Kn), gonadosomatic index (GSI), liposomatic index (LSI), hepatosomatic index (HSI) and somatosomatic index (SSI). The Kn and GSI presented significant temporal differences in both sexes, showing highest values from december to february, coincident with the reproductive cycle. The LSI displayed values close to cero not showing a stable trend, whereas the HSI presented highest and lowest values from may to july and from april to september respectively for both sexes. Finally the SSI exhibited differences between sexes with the maximum values between march and september. Males showed a positive and significant relationship between Kn and WT. In females this pattern was also noted between GSI and LH and between KN vs WT, but was negative between GSI vs SSI and SSI vs LH. We conclude that the use of different biological indices in this species allows following the maturation cycle and their associated metabolic processes being the observed variation patterns related to high seasonally physiological processes.